2017
DOI: 10.1007/s13311-017-0532-0
|View full text |Cite
|
Sign up to set email alerts
|

From Gene to Behavior: L-Type Calcium Channel Mechanisms Underlying Neuropsychiatric Symptoms

Abstract: The L-type calcium channels (LTCCs) Ca1.2 and Ca1.3, encoded by the CACNA1C and CACNA1D genes, respectively, are important regulators of calcium influx into cells and are critical for normal brain development and plasticity. In humans, CACNA1C has emerged as one of the most widely reproduced and prominent candidate risk genes for a range of neuropsychiatric disorders, including bipolar disorder (BD), schizophrenia (SCZ), major depressive disorder, autism spectrum disorder, and attention deficit hyperactivity d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
88
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 368 publications
(510 reference statements)
2
88
0
1
Order By: Relevance
“…Of the multiple classes of Ca v channels, Ca v 1 L-type channels are key mediators of Ca 2+ signals controlling neurogenesis (Marschallinger et al, 2015; Temme et al, 2016; Volkening et al, 2017), neurite growth (Audesirk et al, 1990; Robson and Burgoyne, 1989; Roehm et al, 2008; Schindelholz and Reber, 2000), and gene transcription (Dolmetsch et al, 2001; Graef et al, 1999; Oliveria et al, 2007). Mutations affecting the major Ca v 1 channels in the brain, Ca v 1.2 and Ca v 1.3, are linked to a variety of neurological and psychiatric disorders (Kabir et al, 2017; Pinggera and Striessnig, 2016). Thus, factors that regulate Ca v 1 channels may be critical for maintaining the balance between normal and diseased states of the nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…Of the multiple classes of Ca v channels, Ca v 1 L-type channels are key mediators of Ca 2+ signals controlling neurogenesis (Marschallinger et al, 2015; Temme et al, 2016; Volkening et al, 2017), neurite growth (Audesirk et al, 1990; Robson and Burgoyne, 1989; Roehm et al, 2008; Schindelholz and Reber, 2000), and gene transcription (Dolmetsch et al, 2001; Graef et al, 1999; Oliveria et al, 2007). Mutations affecting the major Ca v 1 channels in the brain, Ca v 1.2 and Ca v 1.3, are linked to a variety of neurological and psychiatric disorders (Kabir et al, 2017; Pinggera and Striessnig, 2016). Thus, factors that regulate Ca v 1 channels may be critical for maintaining the balance between normal and diseased states of the nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years, several studies have identified common single polymorphisms (SNPs) in calcium voltage-gated channel subunit alpha 1C (CACNA1C) and ankyrin-3 (ANK3) in BD patients, implicating these as susceptibility genes for BD [42,43] depletion and are critical for normal brain development and plasticity [44,45] and ankyrin directly interacts with the ER 1,4,5-inositol triphosphate receptor (IP3R), which is localized at MAMs and is responsible for ER Ca 2+ release [46]. Carriers of the CACNA1C risk polymorphism rs1006737 exhibit greater age-related thickness of cortical brain areas widely associated with mood regulation in BD [47].…”
Section: + Dyshomeostasis and Cytoskeleton Abnormalitiesmentioning
confidence: 99%
“…L-type VGCCs are known to play a central role in controlling activity-dependent synaptic plasticity [15-17]. Ca v 1.2 channels, the predominant form of L-type VGCCs in the mammalian brain, are ideally situated somato-dendritically to link neuronal activation to calcium signalling and the regulation of gene expression [15, 16].…”
Section: Introductionmentioning
confidence: 99%